Correlation between pre-admission blood pressure and outcome in a large telestroke cohort. (April 2019) - Sweid, Ahmad; Atallah, Elias; Saad, Hassan; Bekelis, Kimon; Chalouhi, Nohra; Dang, Sophia; Li, Jonathan; Kumar, Ayan; Turpin, Justin; Barsoom, Randa; Tjoumakaris, Stavropoula; Hasan, David; et al.
Highlights: We didn't observe any statistical association between SBP variation and long term clinical outcome. We didn't observe association between SBP during the acute phase and clinical outcome. We advocate lowering SBP to <185 mmHg to increase IVrt-PA eligibility rates. We recruited new stroke patients eligible for MT through the TS network. 38% of MT patients had an mRS ≤ 2 on their last follow-up visit. Fulfilling new strategies and approaches to stroke patients leads to better results. Abstract: Background: Telemedicine rapidly connects patients, with acute ischemic stroke symptoms, with neurovascular specialists for assessment to reduce chemical thrombolysis delivery times. Management of AIS includes maintaining target systolic blood pressures (SBP). In this retrospective study, we assess the efficacy of the telestroke (TS) system at a primary stroke center and the prognostic value of SBP throughout the transportation process. Methods: Patients presenting with acute-onset neurological symptoms to the TS hospitals network, over a 5-year period, were assessed. Those with a confirmed diagnosis of AIS were included. We examined demographics, presenting-NIHSS, last SBP before transfer from the network hospital and continuous BP during transport, stroke risk factors, hospital-course, door-to-needle (DTN) time, treatments, and modified Rankin Scale(mRS). Multivariate analysis was conducted to evaluate the prognostic value of SBP on stroke outcome. Results: Of 2, 928 patients identified, 1, 353 were diagnosed with AIS. Mean age was 66.6 years (SD = 15.4), 47.6% female. Most cases affected the MCA(44.5%). Mean presenting-NIHSS was 8.67(SD = 8.38) and mean SBP was 148 mmHg(SD = 25.39). 73.2% treated using a standard protocol, 23.7% given IVrt-PA, and 6.8% received mechanical thrombectomy(MT). Mean DTN was 96 min(SD = 46; 27.3% <60 min). Age, presenting-NIHSS and pre-existing hypertension were associated with higher mortality and/or higher mRS. SBP was not associated with higher mortality and morbidity. Conclusions: This study displays better clinical outcomes at latest follow-up when compared to current international TS studies. SBP during transportation to the hub hospital did not prove to be a useful prognostic metric. However, future studies should address the limitations of this study to confirm these findings.